The species of Tibetisoperla (Plecoptera: Perlodidae) - Yan, Yan-Hua; Chen, Zhen-Ning; Bozdoğan, Hakan; Li, Wei-Hai (European Journal of Taxonomy, 2022)
Two new species of the hitherto monotypic Tibetisoperla Huo & Du, 2021, T. elongata sp. nov., T. sclerotica sp. nov., are described, illustrated and compared with the type species and other Isoperlinae. Tibetisoperla and T. wangluyui Huo & Du, 2021 are newly recorded for Qinghai Province.